Qatpar Skarngreisen Tungsten Deposit, Central Kazakhstan; Granite-related ore deposits of Central Kazakhstan and adjacent areas - Mazurov A. K. Aleksey Karpovich (1996, 1996)
В фонде НТБ ТПУ отсутствует